Kajian Kritis Tradisi Nyongkolan dalam Perkawinan Adat Lombok Perspektif Urf - Dani, Muhammad Iwan; Rahmawati, Nita Putri (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2024)
The practice of Nyongkolan in traditional marriages of Lombok people has been in the spotlight because it causes traffic jams, drinking alcohol, and causes brawls. This study aims to examine the current Nyongkolan tradition and its suitability with Sasak characteristics and Islamic teachings from the perspective of 'Urf. The research method uses qualitative research with data collection through observation and documentation. The data analysis method uses Miles and Huberman data analysis through the stages of data reduction, data presentation, and conclusion drawing. The results showed that basically in the view of 'Urf the implementation of Nyongkolan is allowed as long as it does not conflict with Islamic law. In the beginning, the Nyongkolan tradition was carried out to take the newlyweds to the female family's house and announce the girl's marriage in the hope that no one would disturb the two brides because they had entered into a legal marriage. The practice of Nyongkolan becomes haram when it is accompanied by erotic dancing, drinking alcohol, and brawls because it is contrary to Islamic teachings.